Enantiodivergent Synthesis of Both PAMPO Enantiomers Using l-Menthyl Chloroacetate and Stereomutation at P in Classical Quaternisation Reactions - Dziuba, Kamil; Lubańska, Małgorzata; Pietrusiewicz, K. Michał (Synthesis, 2020)
A practical protocol for efficient synthesis of both PAMPO enantiomers as well as related functionalised P-stereogenic phosphine oxides in 1–3 steps from effectively resolved (SP)-l-menthyl o-anisyl-(phenyl)phosphinylacetate has been developed. Examples of non-stereoselective quaternisation of a tertiary phosphine by alkyl halides have been revealed.
Keywords: P-stereogenic phosphine oxides; PAMPO; resolution; phosphines; pyramidal inversion; non-stereoselective quaternisation